(untitled) (Journal of Life and Earth Science, 2014)
Sodium arsenite (NaAsO2) considered effective for aquatic weed control, has been found to be harmful to several species of freshwater teleost fishes. Channa punctata was exposed to NaAsO2 at the concentrations of 100?l/30g and 200?l//30g body weight per fish and cultured for 14 days post exposure respectively. Tissue disorientation, peliosis and vacuolization accompanied by karyolysis, apoptosis and necrosis in the liver and heart were significant on days onwards. Irregularities in the intestines including apoptotic and necrotic cells were also common, enlargement of the mucosa and submucosa was noted. Corresponding with the histopathological lesions, necrosis of liver cells and intestinal functions or induction of heart muscles at the early phase of arsenic exposure may be the possible causes of fish death. DOI: http://dx.doi.org/10.3329/jles.v7i0.20123 J. Life Earth Sci., Vol. 7: 67-70, 2012